Who was affected by the shortage of penicillin for syphilis in Rio de Janeiro, 2013-2017? - Rachel Sarmeiro Araujo; Ana Sara Semeão de Souza; José Ueleres Braga (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To analyze the shortage of benzathine penicillin G (BPG), characterizing its temporal evolution and spatial distribution in the city of Rio de Janeiro from 2013 to 2017. METHODS This ecological study used gestational and congenital syphilis notifications, BPG distribution records, and sociodemographic data from the population of Rio de Janeiro. To quantify the shortage, a BPG supply indicator was estimated per quarter for each neighborhood between 2013 and 2017. Thematic maps were created to identify areas and periods with greater BPG shortage, described according to sociodemographic factors, health services network, and epidemiological features in the incidence of syphilis. RESULTS BPG shortage in Rio de Janeiro from 2013 to 2017 was not homogeneous in space nor in time. The temporal evolution and spatial distribution of BPG scarcity shows that the shortage affected the inhabitants of the municipality in different ways. Shortage was lower in 2013 and 2016 and more severe in 2014, 2015, and 2017, particularly in neighborhoods within the programmatic areas PA3 and PA5, poorer and with higher prevalence rates of gestational and congenital syphilis. CONCLUSIONS Analyzing BPG shortage and its temporal evolution and spatial distribution in Rio de Janeiro allowed us to realize that the inhabitants are affected in different ways. Understanding this process contributes to the planning of actions to face shortage crises, minimizing possible impacts on the management of syphilis and reducing inequality in access to treatment.